Pengaruh Content Marketing dan Live Streaming terhadap Minat Beli Es Momoyo di Besuki Situbondo - Faiqurrahman Faiqurrahman; Ahmad Hafas Rasyidi; Dassucik Dassucik (Universitas Proklamasi 45, 2026)
This study was conducted to examine the extent of the influence of content marketing and live streaming on consumers' purchase intention for Es Momoyo products in the Besuki Situbondo area. The research method used was quantitative, with data collected through questionnaires and analyzed using multiple linear regression, as well as validity, reliability, and classical assumption tests. The results of this study indicate that content marketing and live streaming have a positive and significant effect on purchase intention, both partially and simultaneously. To test the significance (significant or not significant) of the influence of content marketing and live streaming on purchase intention, a partial test was conducted when testing the influence of the content marketing variable, which showed that the calculated t value for (X1) was 2.344; the table t value at a 95% confidence level showed a figure of 1.9858. Because the calculated t value > table t value, H0 is rejected and Ha is accepted, which can be interpreted as there being a significant effect of content marketing on purchase intention. The live streaming variable showed that the calculated t value for (X2) was 4.449; the table t value at a 95% confidence level showed a figure of 1.9858. Because the calculated t value > table t value, H0 is rejected and Ha is accepted, which can be interpreted as there being a significant effect of live streaming on purchase intention. From these results, the variable that most dominantly influences purchase intention is live streaming compared to the content marketing variable.